Evaluasi Kinerja Keuangan Pada PT. Bunas Finance Indonesia (BFI) Tbk - -, Ida Noorpanti (EKONOMIA, 2015)
PT. Bunas Finance Indonesia is one of the auto finance company. The purpose of this study is to evaluate the financial performance. PT. Bunas Finance Indonesia Tbk from years 2011 - 2012 in terms of profitability, liquidity, and solvency. Formulation of the problem raised is "financial performance at PT. Bunas Finance Indonesia Tbk in 2012 increased compared to the financial performance in 2011 ". Basic theory used in this study include the financial statements Management, Investment and analytical tools that are used to measure performance. The hypothesis in this study are "The financial performance of PT. Bunas Finnace Indonesia Tbk in 2012 decreased compared to 2011. Liquidity financial performance represented by the current ratio increased, the cash ratio decreased. Profitability is represented by the return on assets ratio decreaseds, while return on equity increased Solvency ratio represented the ratio of debt to total capital increased and the ratio of long-term debt on its own capital increase. Therefore it is proven that the PT. Bunas Finance Indonesia Tbk in 2012 increased compared to 2011. After comparing and testing the analytical tool used to determine the financial performance. Bunas Finance Indonesia Tbk can be concluded and the results of this study suggest that the level of financial performance of the company as a whole shows that financial performance. Bunas Finance Indonesia Tbk from 2012 experienced a decline in profits compared to the year 2011, the proposed hypothesis is accepted. If you look at the financial performance shows the performance of companies that are not healthy, then how companies manage finances in order to increase profits in the coming years. then posts that do not really give significant results can be suppressed.